INTERDISCIPLINARIDADE NO CURRÍCULO INTEGRADO NA REGIÃO TAPAJÔNICA NA AMAZÔNIA PARAENSE: ANÁLISE DO PROJETO PEDAGÓGICO DO IFPA (Interdisciplinary Studies Journal, 2024)
This study aimed to conduct an analysis of the integrated curriculum in the Tapajós Region, configured by the pedagogical project of the IFPA campus Itaituba. Since, historically, professional education was based on a welfare and dualist perspective, which divided propaedeutic education and technical training. In effect, the curriculum has been presented in a linear, disciplinary and fragmented way. Nevertheless, Integrated Secondary Education (EMI) and the integrated curriculum, linked to the assumptions of integral human formation, establish interdisciplinarity as an educational principle and a possibility to overcome dichotomies and the separatist bias. In this way, the article results from a critical documentary analysis carried out using Bardin's content analysis technique. The results indicate that interdisciplinarity presents itself as a mere methodological resource and directed to the praxis of disciplines and contents of technical training only. This reality highlights the dissonance between the interdisciplinary proposal and integral human formation, as it cannot encompass the multidimensionality of knowledge. Distancing itself from the materialization of Professional Education in an integrated perspective.
Keywords: Interdisciplinarity; Integrated Curriculum; Vocational Education; Integrated High School